2022
DOI: 10.1186/s12864-022-08753-9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the difference of α-amylase and CYP6AE76 gene between polyphagous Conogethes punctiferalis and oligophagous C. pinicolalis by multiple-omics and molecular biological technique

Abstract: Background Conogethes pinicolalis has been thought as a Pinaceae-feeding variant of the yellow peach moth, Conogethes punctiferalis. The divergence of C. pinicolalis from the fruit-feeding moth C. punctiferalis has been reported in terms of morphology, ecology, and genetics, however there is a lack of detailed molecular data. Therefore, in this study, we investigated the divergence of C. pinicolalis from C. punctiferalis from the aspects of transcriptomics, proteomics, metabolomics and bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…During long-term evolution, the amylase sequences also mutate between related species, which makes amylases differ significantly from inexact substrate preferences. Jing et al [18] have demonstrated that α-amylase showed 94% similarity between the Conogethes pinicolalis and its sibling species C. punctiferalis and that α-amylase gene mutations occur in non-homologous conserved regions. Mutations of this type do not cause structural changes, but they may affect changes in α-amylase expression levels and enzyme activity.…”
Section: Sequences and Structure Of Insect α-Amylasesmentioning
confidence: 99%
“…During long-term evolution, the amylase sequences also mutate between related species, which makes amylases differ significantly from inexact substrate preferences. Jing et al [18] have demonstrated that α-amylase showed 94% similarity between the Conogethes pinicolalis and its sibling species C. punctiferalis and that α-amylase gene mutations occur in non-homologous conserved regions. Mutations of this type do not cause structural changes, but they may affect changes in α-amylase expression levels and enzyme activity.…”
Section: Sequences and Structure Of Insect α-Amylasesmentioning
confidence: 99%
“…In addition, they metabolize many exogenous substances (such as pesticides, plant secondary substances and other environmental chemicals), and this has detoxification and activation effects ( Yang and Liu, 2011 ; Giraudo et al, 2015 ). Many insect P450 genes, especially in the families of CYP3 and CYP4, participate in the detoxification of, and metabolic resistance to, several insecticides ( Amenya et al, 2008 ; Balabanidou et al, 2016 ; Wang et al, 2019 ; Jing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports found that the mRNA expression levels of CYP6CV1 and CYP6AB51 in CYP6 family from C. punctiferalis were upregulated when larvae fed on resistant plant, and in other lepidopteran insects, the CYP6 family genes also played important role in the insect resistance to some pesticides ( Chen et al, 2015 ; Jing et al, 2022 ). To examine whether CYP6CV1 and CYP6AB51 in C. punctiferalis also are involved in the detoxification of the commonly used pesticides, they were identified and characterized by molecular technologies.…”
Section: Introductionmentioning
confidence: 99%